توأمة وكالات السياحة والأسفار في الجزائر ودورها في تشجيع السياحة الداخلية (وكالات السياحة بالشلف وتمنراست) - سماعيل حسيبة; سعيدي حمزة (جامعة الوادي University Of Eloued, 2024)
تهدف هذه الورقة البحثية إلى ابراز أهمية ودور توأمة وكالات السياحة والأسفار في تشجيع السياحة الداخلية في الجزائر من خلال إقامة اتفاقيات تعاون بين مختلف الفاعلين السياحيين عن طريق خلق ديناميكية تبادل وتوأمة بين وكالات السياحة والأسفار الناشطة في الشمال ووكالات السياحة والأسفار الناشطة في الجنوب ،وقد اعتمد الباحثان على المنهج الاستنباطي بأسلوبيه الوصف التحليل في محاولة لمعرفة كيفية إنشاء وكالات السياحة والأسفار الذي يتمثل دورها أساسا في التعريف بالمؤهلات السياحية مساهمتها في تنشيط السياحة الداخلية بالتركيز على السياحة الساحلية والسياحة الصحراوية وقد تم اختيار ولايتين موضع الدراسة الشلف في الشمال وتمنراست في الجنوب. وقد أظهرت النتائج على ضرورة انتهاج أساليب حديثة في تطوير نماذج جديدة للشراكة وتعزيز التبادل والتعاون لوكالات السياحة والأسفار الشمالية والجنوبية في الجزائر مع إبراز المعوقات التي تواجههم في هذا الصدد ، واقتراح مجموعة من التوصيات من شأنها أن تعطي دفعا لهذا التعاون . This research paper aims to highlight the importance and role of twinning between travel and tourism agencies in promoting internal tourism in Algeria. This is achieved through the establishment of collaborative agreements among various tourism stakeholders by creating a dynamic exchange and twinning between active travel and tourism agencies in the north and those in the south. The researchers adopted the inductive method using both descriptive and analytical approaches to understand how these travel and tourism agencies are established, primarily focusing on their role in identifying touristic qualifications and their contribution to stimulating Internal tourism, particularly emphasizing coastal and desert tourism. Two specific regions were selected for the study: Chlef in the north and Tamanrasset in the south. The results indicated the necessity of adopting modern methods to develop new partnership models and enhance exchange and collaboration between northern and southern travel and tourism agencies in Algeria. Moreover, the study highlighted the obstacles encountered in this regard and proposed a set of recommendations aimed at fostering this cooperation.
The twinning of travel agencies in Algeria and their role in promoting domestic tourism - Chlef and Tamanrasset tourism agencies
Keywords: توأمة وكالات السياحة والأسفار; سياحة داخلية; سياحة ساحلية; سياحة صحراوية; سائح داخلي; Twinning of travel and tourism agencies; Internal tourism; coastal tourism; desert tourism; Internal tourist